Protocol for an integrated phase II/III randomised controlled trial of transarterial chemotherapy and sorafenib with or without stereotactic body radiation therapy in patients with nonmetastatic unresectable hepatocellular carcinoma - Chopra, Supriya; Shetty, Nitin; Goel, Mahesh; Engineer, Reena; Rajamanickam, Karthick; Kulkarni, Suyash; Polnaya, Ashwin; Patkar, Shradha; Ostwal, Vikas; Ramadwar, Mukta; Swamidas, Jamema; Phurailatpam, Reena; et al. (International Journal of Clinical Trials, 2017)
Background: Vast majority of patients with hepatocellular carcinoma (HCC) present with unresectable disease. In the last decade results of randomized trials and subsequent meta-analyses established trans-arterial chemoembolization (TACE) as standard of care in patients with Barcelona clinic liver cancer (BCLC) stage B. However, there is clearly a need to investigate additional therapeutic options that would consolidate the initial response to TACE. A recent meta-analyses concluded that addition of radiation to TACE had 10-35% improvement in two-year overall survival, however as results of meta-analyses were based on small studies, the need for conducting a high quality randomized study was highlighted. The present study is designed to investigate the role of high dose stereotactic radiation as consolidation therapy after TACE in patients with non-metastatic unresectable HCC. Methods: Patients diagnosed with non-metastatic unresectable HCC with BCLC stage B/A (medically inoperable) and Child-Pugh’s score A-B7 will be eligible. The trial will randomize patients into TACE alone arm or TACE followed by stereotactic body radiation therapy (SBRT). The primary aim is to compare in-field progression free survival (PFS) in phase II and overall survival in phase III between the control (TACE) and intervention arm (TACE+SBRT). The secondary aim is to compare cause specific survival, imaging response and quality of life in control and intervention arms. Results: First analysis of the study has been planned when patient accrued under phase II study have completed 1 year follow up. Trail Registration: Clinicaltrials.gov,NCT02794337